Evaluation of cold tolerance in sorghum germplasm from the Chishui River Basin in China: insights from germination, field trials, and physiological assays - Yang, Hongli; Cui, Wenxue; Liu, Yue; Zhang, Wen; Liu, Jiangli; Liu, Qing; Yao, Hangmei; Huang, Yue; Tang, Jiadai; Wu, Kaixian (Frontiers in Plant Science, 2025)
IntroductionExploring cold-tolerant sorghum germplasm is crucial for improving production in low-temperatures regions. However, the cold tolerance of local sorghum germplasms in the Chishui River Basin, located in the southwestern China, remains poorly characterized.MethodsWe evaluated 71 sorghum germplasms at Maotai Institute from 2022 to 2024 using germination tests, pot trials, and field experiments with a two-factor design. Germination potential, germination percentage, and seedling vigor traits (plumule and radicle length and weight) varied significantly among the 71 sorghum germplasm (P < 0.01). Membership function method identified several highly cold-tolerant accessions (e.g., Nos. 12, 22) and cold-sensitive ones (Nos. 17, 44), establishing 15 °C as an optimal temperature for germination stage cold tolerance assessment.ResultsCluster analysis classified these into four groups: cold-tolerant (11), moderately cold-tolerant (22), moderately cold-sensitive (29), and cold-sensitive (9). Agronomic data collected under two early sowing conditions (severe and mild low-temperature stress) demonstrated that several germplasm accessions, like No. 12, maintained high emergence rates (97% and 100% VS. 100% in conventional sowing) and grain weight per panicle (63.3 g and 53.4 g VS. 45.9 g in conventional sowing) without significant reductions, whereas others, such as Nos. 17 and 48, showed marked decreases (P < 0.01). The superior cold tolerance of accessions Nos. 2, 12, and 22 was confirmed through membership function analysis (D-value > 0.6). A significant positive correlation between comprehensive cold tolerance ratings at both the germination and field stages was observed (r = 0.687, P < 0.05). Cold-tolerant germplasms such as No. 12 exhibited high cold tolerance coefficients for chlorophyll content (CHL: 0.98), relative water content (RWC: 0.99), superoxide dismutase (SOD: 1.77), and peroxidase (POD: 2.03), and low malondialdehyde (MDA: 1.20), indicating enhanced membrane stability and oxidative stress tolerance (P < 0.05). Stepwise regression highlighted a strong correlation (r = 0.976, P < 0.01) between predicted values and field D-values, identifying SOD and POD activities as critical physiological indicators of cold tolerance.ConclusionThis study not only identifies valuable cold-tolerant sorghum germplasms but also elucidates their physiological mechanisms, providing essential insights and materials for developing cold-tolerant varieties and resilient cultivation practices in the Chishui River Basin.